# Example 26 - Chapter 9 Class 12 Differential Equations (Term 2)

Last updated at Dec. 11, 2019 by Teachoo

Examples

Example 1 (i)

Example 1 (ii) Important

Example 1 (iii) Important

Example 2

Example 3 Important

Example 4 Deleted for CBSE Board 2022 Exams

Example 5 Deleted for CBSE Board 2022 Exams

Example 6 Important Deleted for CBSE Board 2022 Exams

Example 7 Deleted for CBSE Board 2022 Exams

Example 8 Deleted for CBSE Board 2022 Exams

Example 9

Example 10

Example 11

Example 12 Important

Example 13

Example 14 Important

Example 15 Important

Example 16

Example 17 Important

Example 18 Important

Example 19

Example 20 Important

Example 21 Deleted for CBSE Board 2022 Exams

Example 22 Important

Example 23 Important

Example 24

Example 25 Deleted for CBSE Board 2022 Exams

Example 26 You are here

Example 27 Important

Example 28 Important Deleted for CBSE Board 2022 Exams

Chapter 9 Class 12 Differential Equations (Term 2)

Serial order wise

Last updated at Dec. 11, 2019 by Teachoo

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. Since your board exams are coming, why not help Teachoo create more videos and content by supporting us? Please click on this link to make a donation

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. Since your board exams are coming, why not help Teachoo create more videos and content by supporting us? Please click on this link to make a donation

Example 26 Find the particular solution of the differential equation log(ππ¦/ππ₯)=3π₯+4π¦ given that π¦=0 π€βππ π₯=0 log(ππ¦/ππ₯)=3π₯+4π¦ ππ¦/ππ₯ = e(3x + 4y) ππ¦/ππ₯ = e3x e4y Separating the variables ππ¦/π^4π¦ = e3x dx eβ4y dy = e3x dx Integrating both sides β«1βγπ^(β4π¦) ππ¦γ=β«1βπ^3π₯ ππ₯ π^(β4π¦)/(β4)=π^3π₯/3+πΆ 0=π^3π₯/3+π^(β4π¦)/4+πΆ π^3π₯/3 + π^(β4π¦)/4 + C = 0 (4π3π₯" + " 3π^(β4π¦))/12 + C = 0 (4π3π₯" + " 3π^(β4π¦) + 12πΆ)/12 " = 0" 4π^3π₯ + 3π^(β4π¦) + 12C = 0 Given y = 0 when x = 0 β¦(1) Putting x = 0 & y = 0 in (1) 4π^(3(0)) + 3π^(β4(0)) + 12C = 0 4π^0 + 3π^0 + 12C = 0 4 + 3 + 12C = 0 7 + 12C = 0 12C = β 7 C = (β7)/12 Putting value of C in (1) 4π^3π₯ + 3π^(β4π¦) + 12C = 0 4π^3π₯ + 3π^(β4π¦) + 12((β7)/12) = 0 ππ^ππ + ππ^(βππ) β 7 = 0